Worker-machine relationship based strategy for sustainable management in a machine shop - Shiela Mhay R. Dalisay; Arnie Lyn D. Alagos; Charmine Sheena R. Saflor; Klint Allen A. Marinas; Yung- Tsan Jou (Research Synergy Foundation, 2022)
Nowadays, founding a sustainable control method will assist institutions in utilizing resources effectively and efficiently and enable the firm to have a competitive edge for an extended period. A worker-machine relationship-based strategy has been oriented in a machine shop where the process cost is elevated and resources are ineffective. Multiple investigations probed the usefulness of various problem-solving instruments in diverse fields; nevertheless, there is a deficiency of investigations on the application of gang process charts, and random and synchronous servicing, mainly in a machine shop. Consequently, this analysis sought to assess the job distribution during service procedure, decide which employee and machine will need reassignment to perform effectively, and suggest a sustainable management technique to optimize the process and downsize operation costs. This study employed a descriptive research design with an overt observational approach in a well-established machine shop in Oriental Mindoro, Philippines. A sum of fifteen workers straight engaged with the machines has been observed. The study realized that Operators 1,2,3,4, and 5 are already working on the perfect number of machines. Operator 6 will need one additional machine, and Operators 7,8, 9, and 10 will need one less machine to perform on ideal quantity and support operating costs. None of the machines will require modifications in the number of operators due to nuanced machine downtime. Moreover, the total anticipated cost of reassignments is not invariably declining. Accordingly, counting on the fee of the firm's services, the administrator or manager may enforce the modifications.